Social stigma and self-perception in adolescents with tourette syndrome - Cox JH; Nahar A; Termine C; Agosti M; Balottin U; Seri S; Cavanna AE (Dove Medical Press, 2019)
Joanna H Cox,1 Ananda Nahar,2 Cristiano Termine,3 Massimo Agosti,4,5 Umberto Balottin,6,7 Stefano Seri,8 Andrea E Cavanna8–101Sandwell and West Birmingham NHS Foundation Trust, Birmingham, UK; 2University Hospitals Birmingham NHS Foundation Trust, Birmingham, UK; 3Child Neuropsychiatry Unit, Department of Medicine and Surgery, University of Insubria, Varese, Italy; 4Neonatology Unit, Department of Maternal and Child Health, Del Ponte Hospital, Varese, Italy; 5Paediatric Unit, Department of Medicine and Surgery, University of Insubria, Varese, Italy; 6Child Neuropsychiatry Unit, IRCCS Mondino Foundation, Pavia, Italy; 7Child Neuropsychiatry Unit, Department of Brain and Behavioural Sciences, University of Pavia, Pavia, Italy; 8School of Life and Health Sciences, Aston Brain Centre, Aston University, Birmingham, UK; 9Department of Neuropsychiatry, Birmingham and Solihull Mental Health NHS Foundation Trust (BSMHFT) and University of Birmingham, Birmingham, UK; 10Sobell Department of Motor Neuroscience and Movement Disorders, Institute of Neurology and University College London, London, UKAbstract: Tourette syndrome (TS) is a complex neurodevelopmental disorder characterized by multiple motor and vocal tics, which commonly presents with multiple behavioral problems, including co-morbid attention-deficit and hyperactivity disorder and obsessive-compulsive disorder. Both tics and co-morbid conditions have been shown to potentially affect patients’ health-related quality of life. While TS typically presents in childhood, its manifestations peak in severity during adolescence, a critical period in which affected individuals are exposed to potential stigma from peers. Physical and behavioral manifestations can also contribute to stigma, which subsequently leads to poorer health outcomes, discrimination, and a reduced willingness to seek help. The available evidence suggests that young patients with TS can experience reduced social acceptance from peers and difficulties establishing relationships. There is also evidence that some health care professionals share the unhelpful belief that young patients with TS should be disciplined in order to correct their disruptive behavior, based on the erroneous assumption that tics can be consciously controlled. Studies focussed on self-perception in patients with TS have yielded inconsistent results, with some studies showing problems in the domains of self-concept and self-esteem. Feelings of isolation, loneliness, and experiences of bullying have been reported more consistently. Interventions are required to reduce misconceptions about the condition and thus reduce stigma through targeted education and behavioral interventions. A multi-faceted approach that focuses on educating children, adults, and educators about TS would be beneficial to help alleviate stigma. This can be combined with self-advocacy and tailored psychological therapies for young patients with TS. The present paper reviews the current literature on stigma and self-perception in adolescents with TS in order to inform clinical decisions about management strategies and possible interventions to improve health-related quality of life.Keywords: tourette syndrome, tics, stigma, self-perception, adolescents